(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the content of professional-pedagogical competence of future teachers, forms and methods of its improvement, qualities of professional competence and their essence. In improving the professional competence of the future specialist, the stages of work on oneself, forms of self-evaluation through self-development, analysis and monitoring are given. The necessity of developing innovative special programs for improving professional and pedagogical competence, proposals and recommendations on its components were developed, conclusions were presented.